Does Insurgent Selective Punishment Deter Collaboration? Evidence from the Drone War in Pakistan - Bauer, Vincent; Reese, Michael; Ruby, Keven (The Journal of conflict resolution, 2022)
Scholars of civil wars have long argued that non-state actors can use selective punishment to reduce collaboration with state adversaries. However, there is little systematic evidence confirming this claim, nor investigation into the mechanisms at play. In this paper, we provide such evidence from the drone war in Pakistan. Militants in Pakistan’s tribal areas engaged in a brutal counterespionage campaign with the aim of reducing collaboration with the United States. Our analysis combines a novel dataset of collaborator killings with data on drone strike outcomes. We find that strikes killed half as many militant leaders and fighters following collaborator killings and that this suppressive effect likely works by deterring spying in the future. Beyond providing an empirical confirmation of the selective punishment hypothesis, our paper suggests an unacknowledged vulnerability of the drone program to reprisals against local allies and collaborators that limits its effectiveness as a long-term tool of counterterrorism.